Does relationship matter? – Customers' response to service failure. Issue 2 (4th March 2014) - Tsai, Chia-Ching; Yang, Yung-Kai; Cheng, Yu-Chi
Abstract : Purpose: – The purpose of this paper is to examine how service failure affects customers' negative response and how service recovery affects perceived justice in the context of different relationship norms. Design/methodology/approach: – It includes four studies that examine how relationships influence customer reactions to service failures. In study 1, the paper examines how service failures affect customers' negative reaction. In study 2, the paper examines how service recoveries influence perceived justice. Study 3 and study 4 test the robustness of the results of study 1 and study 2. All studies have a 2×2 between-subjects design. Findings: – The results show that individuals in exchange relationships experience a stronger feeling of betrayal than those in communal relationships during service failures. Further, individuals feel more betrayed and show greater negative responses during process failures. They perceive greater justice when offered physical recoveries, which, in turn, contributes to higher service-recovery satisfaction. Research limitations/implications: – This study was conducted in Taiwan. Customer reactions to service failures may vary according to cultural and environmental contexts. Practical implications: – Service providers are encouraged to cultivate relationships with customers and identify different types of customers to compensate them more effectively, according to their preferences. Originality/value: – This study introduces relationship norms to investigate consumer responses to service failures. The main contributions are twofold; it investigates the effect of relationship norms on customer responses to service-failure types and service-recovery types.